Examining After-School STEM Programs: Insights and Recommendations - Cardullo, Vicky; Burton, Megan; DeJoong , Anna Claire (Social Education Research, 2026)
Effective after-school Science, Technology, Engineering and Mathematics (STEM) programs require multiple elements and instructional practices that intentionally support engagement and growth of all learners across varied early learning contexts. This study contributes to the current literature by examining instructional quality across eight early learning environments and changes made following the implementation of a Dimensions of Success (DoS)-informed observation process. Using pre-and post-observation data of informal early learning STEM centers, the study investigates patterns across four key dimensions of practice: environment, engagement, knowledge, and relationships. Analyses include both dimension-level trends and site-level mean scores to capture variation within and across programs. Findings indicate overall positive gains in instructional quality following receiving feedback obtained from the observation process, suggesting that communicating results of structured, research-based observational frameworks can support improvement in STEM-focused early learning and out-of-school settings. However, because observational feedback was not accompanied by sustained professional development or ongoing coaching between observation cycles, growth was uneven across sites and dimensions. These results highlight the potential for greater and more consistent improvement when observation-based feedback is coordinated with continuous, targeted professional support. This work can inform effective change by educators, program leaders, and policymakers to support engaging informal STEM experiences. By examining areas for growth and change that are aligned with research-based practices for informal early childhood STEM experiences and instructional improvement, educators, program leaders, and policymakers can make more informed choices when seeking to enhance equity, inclusion, and instructional quality in after-school STEM programs.